2013
DOI: 10.1016/j.jebo.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Group membership, team preferences, and expectations

Abstract: Group membership is a powerful determinant of social behaviour in a variety of experimental games. Its effect may be channelled primarily via the beliefs of group members, or directly change their social preferences. We report an experiment with a prisoner's dilemma with multiple actions, in which we manipulate players' beliefs and show that group identity has a consistent positive effect on cooperation only when there is common knowledge of group affiliation. We also test the robustness of the minimal group e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 37 publications
1
46
1
1
Order By: Relevance
“…Evidence has shown that group identity affects interaction attitudes, such as reciprocity concerns, altruism, and the willingness to cooperate or punish (Bernhard et al, 2006;Chen and Li, 2009;Fershtman and Gneezy, 2001;Goette et al, 2006;Guala et al, 2013). Beginning with the pioneering work of Tajfel (1970), it has been extensively documented that individuals favor ingroup members, which suggests that a transfer to an in-group member yields higher utility than does a transfer to an out-group individual.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that group identity affects interaction attitudes, such as reciprocity concerns, altruism, and the willingness to cooperate or punish (Bernhard et al, 2006;Chen and Li, 2009;Fershtman and Gneezy, 2001;Goette et al, 2006;Guala et al, 2013). Beginning with the pioneering work of Tajfel (1970), it has been extensively documented that individuals favor ingroup members, which suggests that a transfer to an in-group member yields higher utility than does a transfer to an out-group individual.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical and experimental studies have stressed social and cultural factors, altruism and "warm glow" or merely the preference for cooperation, as important determinants of pro-social cooperative behavior (Andreoni, 1995, Crumpler and Grossman, 2008, Andreoni and Payne, 2011, Guala et al, 2013. In line with this literature, we consider in this paper that even while taking decisions individually, individuals remain social beings.…”
Section: Introductionmentioning
confidence: 83%
“…This feeling contributes to the individual's decision process. We therefore consider that individuals can behave as members of a group, i.e., be team-reasoning, acting under a "common knowledge of solidarity" (Bacharach, 1999;Bacharach et al 2006;Guala et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to how Guala et al (2012) induced groups in one of their treatments, participants in this experiment drew from a covered box at the entrance of the laboratory either a yellow or red arm band which indicated their group identity and their computer number that also determined whether they are Player 1 or Player 2. 17 Each participant is assigned a visually isolated computer terminal that corresponded to the number indicated on their arm band.…”
Section: Procedures and Payoffsmentioning
confidence: 99%